68Ga-FAPI PET/CT Versus 18F-FDG PET/CT for the Evaluation of Disease Activity in Takayasu Arteritis. (October 2021) - Wu, Simin; Pang, Yizhen; Zhao, Liang; Zhao, Long; Chen, Haojun
Abstract : Abstract: Evaluation of disease activity in Takayasu arteritis (TA) is challenging because clinical, biological, and imaging data do not always correlate. In this case, a 19-year-old woman with TA underwent 18 F-FDG PET/CT for evaluating disease activity. However, no abnormal 18 F-FDG uptake was observed in the large arteries. Follow-up with 68 Ga-FAPI PET/CT showed intense activity in the mildly thickened walls of bilateral carotid, subclavian arteries, and thoracic and abdominal aorta. This case presented an example where 68 Ga-FAPI outperformed 18 F-FDG for detecting active inflammation of TA. Therefore, 68 Ga-FAPI PET/CT may allow monitoring of disease activity and facilitate selecting the optimal therapy for TA patients.